Gather grateful - Litwin, Megan (Candlewick Press, 2025)
"Lyrical prose and luminous illustrations welcome the arrival of fall in a season of community and thanksgiving. As colors in nature start to change, animals begin gathering items -- squirrels their acorns, crows their treasures, raccoons the bits and pieces needed to fortify their homes. Animals of all species prepare to gather with each other too, for warmth, for affection, for sharing food or stories. With lilting, rhythmic prose, Megan Litwin heralds the beginning of the season and follows the transition of animals and humans as they prepare for the coming winter. Alexandra Finkeldey's striking limited palette, capturing the preparations outside and in, brings this story of love and gratitude to quietly glowing life."--